Fatty Acid-Binding Proteins in Psoriasis—A Review - Julia Nowowiejska; Anna Baran; Iwona Flisiak (Metabolites, 2022)
Psoriasis is one of the most common skin diseases in dermatological practice. It affects about 1–3% of the general population and is associated with different comorbidities, especially metabolic syndrome. Fatty-acid-binding proteins (FABPs) are a family of cytosolic proteins which are an important link in lipid metabolism and transport; moreover, they have different tissue specificity and properties. So far, ten FABPs have been discovered and seven have been investigated in psoriasis. In this review, we discuss the nature of all FABPs and their role in psoriasis. FABPs have different organ and tissue expression, and hence various functions, and may be markers of different disorders. Considering the concentration of a few of them tends to be elevated in psoriasis, it confirms the current perception of psoriasis as a multiorgan disorder associated with plenty of comorbidities. Some FABPs may be also further investigated as biomarkers of psoriasis organ complications. FABP-1 and FABP-5 may become potential markers of metabolic complications and inflammation in psoriasis. FABP-7 could perhaps be further investigated as an indicator of the neurodegenerative processes in psoriatic patients.